Runtime verification approach for DoS attack detection in edge servers - Bin YU; Nan ZHANG; Xu LU; Zhenhua DUAN; Cong TIAN (Tongxin xuebao)
Aiming at the DoS (denial of service) attacks against edge servers in an edge computing system, a parallel runtime verification approach for DoS attack detection was proposed.First, PPTL (propositional projection temporal logic) formulas were utilized to formally describe expected behaviors of an edge server and DoS attack characteristics.Then, for the PPTL formulas to be verified, a parallel runtime verification framework was adopted to make use of the computing and storage resources of an edge server to conduct anomaly detection and misuse detection.The proposed attack detection approach was performed for an actual P2P (peer-to-peer) network based on smart parking system using edge computing which was supposed to suffer from a DoS attack.Experiments show that the proposed method can accurately and efficiently identify abnormal behaviors of edge servers and types of DoS attacks.